Somatic embryogenesis in holm oak male catkins - Blasco, M.; Barra, A.; Brisa, C.; Corredoira, E.; Segura, J.; Toribio, M.; Arrillaga, I. (Plant Growth Regulation, 2013)
Somatic embryogenesis (SE) of tree species is the most promising method for the implementation of multivarietal forestry and for biotechnological approaches. To date, however, the application of this technology to mature trees is restricted to a few species. This is the first report on the induction of SE from male catkins of 100-year-old holm oaks (Quercus ilex L.). Embryogenic competence was mainly dependent on genotype and restricted to the most advanced catkin developmental stage with distinguishable closed flowers along the axis. Fol- lowing a three-stage treatment procedure, embryogenic response (frequencies up 3.3 %) was obtained in three [Remedio, Villar del Arzobispo (VA) and Hunde (HU)] out of the five genotypes evaluated. In the culture conditions tested, the preferred protocol to induce SE in holm oak catkins should include: induction on MS medium with 6-benzyladenine and naphthaleneacetic acid, subculture onto medium with a reduced concentration of both plant growth regulators and a final transference to medium without growth regulators. Under these conditions cotyledonary-stage cotyledonary-stage somatic embryos developed from brown calli with or without nodular structures. Secondary SE, favored by the addition of sorbitol to the manifestation medium, allowed the establishment of 14 embryogenic lines belonging to VA and HU genotypes. Histological observations of the proliferating cultures revealed the presence of globular, torpedo and cotyledonary somatic embryos. Somatic embryos were diploid as verified by flow cytometry analysis, suggesting that they originated from the perianthic tissue of the male flower
Keywords: adult trees; developmental stage; flow cytometry; forest biotechnology; histology; micropropagation; Quercus ilex; secondary embryogenesis

Microspore-derived embryos from Quercus suber anthers mimic zygotic embryos and maintain haploidy in long-term anther culture. - Bueno, María a; Gomez, Arancha; Sepulveda, Federico; Seguí, José M.; Testillano, Pilar S.; Manzanera, Jose a; Risueño, Maria-Carmen (Journal of plant physiology, 2003)
Microspore-derived embryos produced from cork oak anther cultures after long-term incubations (up to 10-12 months) were analysed in order to determine the genetic variability and ploidy level stability, as well as morphology, developmental pattern and cellular organisation. Most of the embryos from long-term anther cultures were haploid (90.7%), corresponding to their microspore origin. The presence of a low percentage of diploid embryos (7.4%) was observed. Microsatellite analysis of haploid embryos, indicated different microspores origins of the same anther. In the diploid embryos, homozygosity for different alleles was detected from anther wall tissues, excluding the possibility of clonal origin. The maintenance of a high proportion of haploid embryos, in long-term anther cultures, is similar in percentage to that reported in embryos originating after 20 days of plating (Bueno et al. 1997). This suggests that no significant alterations in the ploidy level occurred during long incubations (up to 12 months). These results suggest that ploidy changes are rare in this in vitro system, and do not significantly increase during long-term cultures. Microscopical studies of the microspore embryos in various stages revealed a healthy and well developed anatomy with no aberrant or chimeric structures. The general morphology of embryos appearing at different times after plating, looked similar to that of earlier embryos, as well as the zygotic embryos, indicating that they represent high quality material for cork oak breeding.
The following values have no corresponding Zotero field: accession-num: 12964871
Keywords: Cytochemistry; DNA-Analysis; flow cytometry; haploid embryos; immunocyto- chemistry; Quercus suber L.

Stress-induced formation of haploid plants through anther culture in cork oak (Quercus suber) - Bueno, Maria Angeles; Gomez, Arancha; Boscaiu, Monica; Manzanera, Jose Antonio; Vicente, Oscar (Physiologia Plantarum, 1997)
Induetion of haploid embryos and regeneration of plantlets have been obtained, for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by eulture at 25°C in a simple agar medium without growth regulators. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of' several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytie development of the mierospores and for the induetion of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that, like most forest trees, are still recalcitrant in anther culture.
Keywords: anther culture; Cork oak; flow cytometry; Haploid plants; heat shock; Quercus suber; starvation; Stress